2012
DOI: 10.1016/j.watres.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disinfectant and biofilm on the corrosion of cast iron pipes in a reclaimed water distribution system

Abstract: Chlorine CorrosionReclaimed water distribution system a b s t r a c tThe effects of disinfection and biofilm on the corrosion of cast iron pipe in a model reclaimed water distribution system were studied using annular reactors (ARs). The corrosion scales formed under different conditions were characterized by X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), and scanning electron microscopy (SEM), while the bacterial characteristics of biofilm on the surface were determined using several molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(97 citation statements)
references
References 33 publications
6
84
1
2
Order By: Relevance
“…IRB were considered to promote corrosion either by reductively dissolving the protective ferric oxides or by enhancing corrosion itself (Iwona and Christine, 1999). Nevertheless, recent studies indicated that IRB could play corrosion inhibition roles by forming a protective biofilm or reducing dissolved O 2 diffusion (Dubiel et al, 2002;Herrera and Videla, 2009;Wang et al, 2012).…”
Section: Transformation Of Corrosion Related Bacterial Communitiesmentioning
confidence: 99%
“…IRB were considered to promote corrosion either by reductively dissolving the protective ferric oxides or by enhancing corrosion itself (Iwona and Christine, 1999). Nevertheless, recent studies indicated that IRB could play corrosion inhibition roles by forming a protective biofilm or reducing dissolved O 2 diffusion (Dubiel et al, 2002;Herrera and Videla, 2009;Wang et al, 2012).…”
Section: Transformation Of Corrosion Related Bacterial Communitiesmentioning
confidence: 99%
“…Two different classes of microorganisms cause steel pipes corrosion: aerobic and anaerobic types with completely different types of corrosion reactions [11,24]. Microorganisms influence corrosion in several ways [22]: using oxygen by aerobic organisms leads to formation of anodic areas.…”
Section: Resultsmentioning
confidence: 99%
“…1a, a layer of sediment appeared around the pipe perimeter: tubercles up to 10 mm thick, which resulted in a decrease of effective cross section of the 100 mm pipe by 36 %. The metal surface under sediment has deep ulcers (up to 50% of the wall thickness, Figure 1b In recent years to study the processes occurring in steel and cast iron pipes, people are increasingly using modern methods of pipeline condition monitoring and studying morphology and composition of corrosion deposits [11], including SEM/EDS, which allows reinterpreting the observed facts.…”
Section: Methodsmentioning
confidence: 99%
“…This exopolymer matrix confers resistant properties to the whole system via the limitation of the effectiveness of disinfection by consuming the oxidants used, such as chlorine or chloramines. The inactivation mechanism includes the reductive power of the biofilm itself (Wang et al, 2012) and the slow diffusion of oxidants in the biofilm (Lee et al, 2011). In addition, the resilience of biofilm bacteria exposed to oxidant stress (Mathieu et al, 2009) makes chlorination appear to be a relatively ineffective disinfection procedure against biofilms compared to bulk water bacteria.…”
Section: Resultsmentioning
confidence: 99%